STRATEGI PENINGKATAN PENDAPATAN ASLI DAERAH (Studi Kasus Pada Pemerintah Kabupaten Bangka Barat) - Rina hermawati; nunung runiawati; elisa susanti (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2017)
West Bangka is the district with the highest level of gross regional domestic product (GRDP) in Bangka Belitung Province. However, the average contribution of local own-revenue to local revenue over the last three years was 6.57% and 93.43% still depended on intergovernmental (IG) fiscal transfers (transfers from central government), transfers from the provincial government and other legal local revenues. This study focuses on identifying the challenges faced by local government in enhancing local own-revenues by using qualitative research methods. The results shows that 1) taxpayers who provide the biggest contribution to local revenues derived from state-owned enterprises, while the taxpayer derived from the local population is still low. Residents prefer to spend their money in other regions, such as Bangka Induk. 2) local government has not been able to optimize existing potential, and 3) there is dependence on tin as one of the main sources of livelihood of local residents. The suggestions in this research are as follows: to encourage local government to make urban-biased policies and also to enhance public education in order to create diversified livelihood and to provide insight to the public about the importance of participation in development.